"Dummies, Learning Modeling Made Easy": Improving Modeling Education in Human Factors Research. (September 2022) - Jeon, Myounghoon; Zhang, Yiqi; Bao, Shan; Jeong, Heejin
This panel introduces the current practice of human performance modeling and its applications to Human Factors research and discusses how we can promote modeling education. We argue that there is a necessity for new and more engaging learning tools and environments that can include qualitative and quantitative modeling work in Human Factors curricula to fulfill different levels of approaches in Human Factors research. We hope that this panel can encourage more students and junior researchers to utilize modeling in their work and spark exciting discussions for better modeling practice and education.